Prostatic adenocarcinoma metastasizing to a clear cell renal cell carcinoma: Report of a case - Stefan Milerski; Oliver W. Hakenberg; Andreas Erbersdobler (Human Pathology Reports, 2022)
It is not uncommon that patients with prostate carcinoma simultaneously harbor another malignancy, but cancer-to-cancer metastasis is a rare event. We report the case of a 55-year-old man with prostatic adenocarcinoma that metastasized into a primary clear cell renal cell carcinoma, known to be the most frequent tumor-to-tumor recipient. The implications of this phenomenon with regard to diagnostic and therapeutic considerations are discussed, as well as hypotheses on pathogenetic mechanisms.